Scaffolded, embedded required: information literacy education in undergraduate health sciences. - Smith, Denise A.; Sanger, Stephanie (Journal of the Canadian Health Libraries Association (JCHLA), 2023)
Background: The Health Sciences Library and Bachelor of Health Sciences (BHSc) program at McMaster University worked together to build a multi-year information literacy (IL) curriculum embedded within the program under a suite of courses called Praxis Pathways. Description: Praxis Pathways consists of four Threads. Thread 4: information literacy is the focus of this case report. The authors will describe the multi-year embedded IL curriculum, which is scaffolded to build both IL skills, such as database searching, and introduce students to key conceptual conversations in IL, production, and dissemination. Outcomes: BHSc program graduates in 2023 will be the first to have completed all four years of the Praxis Pathways courses, including the IL program developed and delivered by the library. The authors will describe how the impact of the program will be evaluated qualitatively and quantitatively going forward. Conclusion: Embedded librarianship for multi-year, scaffolded IL education in undergraduate programs continues to be a rarity, despite acknowledgement that one-shot instruction has several limitations. The authors present this case report to share how they embedded a for-credit IL curriculum in an undergraduate program that looks beyond the one-shot, skill-based tutorial and focuses on developing adaptive, information literate lifelong learners.